Larangan Kawin Mojok bagi Pasangan Calon Pengantin Perspektif ‘Urf: Desa Tamansari Kecamatan Wuluhan Kabupaten Jember - Muhammad Maymun; Kholil Mahmudi (Jurnal Syariah dan Hukum Komparatif, 2022)
Mojok marriage is a marriage that is prohibited among the people of Tamansari Village, the people of Tamansari Village believe that when the mojok marriage is forced to be carried out, there is a disaster or disaster that befalls the bride and groom's family, based on this maslah researchers conduct research with the aim of studying and describing the views of the people of Tamansari Village regarding the Prohibition of Mojok Marriage, as well as Review 'urf against Mojok Marriage in Tamansari Village. The method used empirically (field Research) and qualitative approaches that produce qualitative descriptive data, the author in determining respondents using the purposive sampling method in the way that people are considered to know best what we expect. data in the field researchers use the interview method Researchers in analyzing a problem using the theory of analysis 'Urf or custom. The results of the prohibition research are the legacy of the ancestors, and the prohibition deserves to be obeyed because the prohibition is also for the good of the child and the household, in addition to being a society is also neutral about the ban, because every thing depends on each other's beliefs. In terms of the various 'urf is included in the category of al-'urf fi'li (Habits in the form of deeds), when viewed from its scope, it is classified as 'urf khas (special tradition), when viewed in terms of acceptance and rejection it can enter the 'urf that is shahih and it can also enter the 'urf that is fasid